Role of Natural Gas Consumption in the Reduction of CO₂ Emissions: Case of Azerbaijan - Sarvar Gurbanov (Energies, 2021)
Azerbaijan signed the Paris Agreement in 2016 and committed to cut greenhouse gas (GHG) emissions by 35% in 2030. Meanwhile, natural gas has been vital component in the total energy mix of Azerbaijan economy and accounted for almost 65% of the total energy consumption. In the overall electricity mix, natural gas-fired power plants generate 93% of the country's electricity. Since global energy consumption is responsible for 73% of human-caused greenhouse-gas emissions, and CO2 makes up more than 74% of the total, this study investigates possible mitigation effects of the natural gas consumption on CO2 emissions for Azerbaijan. Author employed several cointegration methodologies, namely Bound testing Autoregressive Distributed Lag (ARDL) approach, Fully Modified Ordinary Least Squares (FMOLS), Dynamic Ordinary Least Squares (DOLS), and Structural Time Series model (STSM). Author of this paper found that when the share of natural gas increases 1 percent in the total energy mix, CO2 emission per capita decreases approximately 0.14 percent as a result of the ARDL, FMOLS, and DOLS models. All three models provide cointegration between the share of natural gas in the total energy mix and reduction in CO2 emissions.
Keywords: O13; Q35; 330; CO2; natural gas; renewable energy; electricity security